1994
DOI: 10.3171/jns.1994.80.5.0909
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial dissection of the distal middle cerebral artery as an uncommon cause of distal cerebral artery aneurysm

Abstract: An aneurysmal dissection of a right middle cerebral artery (MCA) branch is described in a 56-year-old woman. The abnormality was an incidental finding on computerized tomography and subsequently appeared on magnetic resonance imaging performed to evaluate the patient for subjective pulsatile tinnitus. The intracranial aneurysm was documented to have enlarged on serial angiography over a 6-week interval. Treatment was believed to be necessary because of the unknown etiology of the aneurysm, with the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 15 publications
0
43
2
Order By: Relevance
“…[1][2][3]5,6,8,9,11,14,[17][18][19][20] Study of the mechanisms of ruptured/unruptured arterial dissection using immunohistochemical findings of lysyl oxidase (Lox) and matrix metalloproteinases (MMPs) in multiple dissecting aneurysms demonstrated that Lox1, MMP-2, and MMP-9 were remarkably expressed in hypertrophic media outside the intima in ruptured dissecting aneurysms, but were expressed in the intima and inside hypertrophic media in unruptured dissecting aneurysms. 17) Our patient was hospitalized with ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]5,6,8,9,11,14,[17][18][19][20] Study of the mechanisms of ruptured/unruptured arterial dissection using immunohistochemical findings of lysyl oxidase (Lox) and matrix metalloproteinases (MMPs) in multiple dissecting aneurysms demonstrated that Lox1, MMP-2, and MMP-9 were remarkably expressed in hypertrophic media outside the intima in ruptured dissecting aneurysms, but were expressed in the intima and inside hypertrophic media in unruptured dissecting aneurysms. 17) Our patient was hospitalized with ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions tend to enlarge gradually and rupture eventually. 8,14) Based on a distal MCA dissecting aneurysm that resulted in intracerebral hemorrhage 4 years after its non-hemorrhagic onset, surgical treatment was strongly recommended if ectatic components are identified. 8) In our patient, preoperative angiography revealed aneurysmal dilatation and a thrombosed mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissecting aneurysms in the middle cerebral artery (MCA) are relatively rare, with 26 reported cases of spontaneous dissecting aneurysms of the MCA, [1][2][3][4][5][6][7][8][9]11,[14][15][16][17][18][19] of which only three were located on the M 3 portion. 6,15,17) We describe a rare case of dissecting aneurysm of the M 3 portion treated through resection and anastomosis of the superficial temporal artery (STA) to the MCA.…”
Section: Introductionmentioning
confidence: 99%
“…10) The typical initial clinical symptoms are sudden appearance of headache and the disturbance of consciousness with hemispheric functional loss. 9) Intracranial dissections of the anterior circulation usually occur in young people. 5,10) Most patients with dissections of the posterior circulation present with subarachnoid hemorrhage.…”
Section: Introductionmentioning
confidence: 99%